Is Ovarian Cancer Being Managed According to Clinical Guidelines? Evidence From a Population-Based Clinical Audit. Issue 9 (1st November 2016) - Sobrero, Simona; Pagano, Eva; Piovano, Elisa; Bono, Lorenzo; Ceccarelli, Manuela; Ferrero, Anna; Macchi, Chiara; Mistrangelo, Marinella; Patriarca, Silvia; Tripodi, Elisa; Zanetti, Roberto; Bertetto, Oscar; et al.
Abstract : Background: In the northwestern Italian region of Piedmont, current statistics on hospitalizations show that surgical treatment for ovarian cancer (OC) is taking place in many small hospitals, as opposed to a more centralized approach. A population-based clinical audit was promoted to investigate whether OC is being managed according to clinical guidelines, identify determinants of lack of adherence to guidelines, and evaluate the association between adherence to guidelines and survival. Patients and Methods: Residents diagnosed with OC in 2009 were identified in the regional hospital discharge records database. All hospitalizations within 2 years from diagnosis were reviewed. Patients were classified according to their initial pattern of care, defined as "with curative intent" (CIPC) if including debulking surgery aimed at maximal cytoreduction. Adherence to guidelines for surgery and chemotherapy and the effects of this adherence on OC survival were investigated with logistic regression and Cox models. Results: The final study sample consisted of 344 patients with OC, 215 (62.5%) of whom received CIPC. Increasing age, comorbidities, and metastases were negatively associated with receiving CIPC. In the CIPC group, surgical treatment was adherent to guidelines in 35.2%, whereas chemotherapy was adherent in 87.8%. Surgical treatment that was adherent to guidelines [hazard ratio (HR), 0.72; 95% confidence interval (CI), 0.45–1.15] and absence of residual tumor (HR, 0.55; 95% CI, 0.32–0.94) were associated with better survival in the CIPC group, and chemotherapy that was adherent to guidelines was associated with a significant reduction in the risk of death (HR, 0.49; 95% CI, 0.28–0.87). Conclusions: Results support the need to reorganize the clinical pathway of patients with OC in the Piedmont Region and the need for better adherence to current guidelines.